Miaphysitism and African Christian Legacy: A Millennium of Resilience and Localization in the Ethiopian Orthodox Tewahedo Church - LOU, Ruizhen (Journal of Research for Christianity in China (JRCC), 2025)
The Ethiopian Orthodox Tewahedo Church, one of Africa’s oldest Christian traditions, traces its origins to the Christianization of the Aksumite Kingdom in the 4th century CE. Through the conversion of King Ezana and the missionary efforts of Frumentius, Christianity became a state ideology, closely tied to the Alexandrian Coptic Church and grounded in Miaphysite theology. During the medieval period, the Church navigated challenges such as Islamic expansion by consolidating monastic networks and aligning with the Solomonic dynasty, which legitimized its rule through the Kebra Nagast narrative. In the modern era, the Church faced Portuguese Jesuit missions, Oromo migrations, colonial resistance, and socialist reforms, ultimately achieving autocephaly in 1959. In the globalized world, it balances the preservation of Ge’ez traditions with competition from Evangelical movements, while its cultural legacy—exemplified by Lalibela’s rock-hewn churches, manuscript art, and Timkat festivals-continues to define Ethiopian national identity. The Church’s resilience and localized adaptation position it as a paradigm of African Christianity.
Keywords: Ethiopian Orthodox Tewahedo Church, Miaphysitism, Kingdom of Aksum, Frumentius, Lalibela Churches